Towards an Ecumenical Hermeneutics of Diversity: Some Remarks on the Hermeneutical Challenges of the Ecumenical Movement - Körtner, Ulrich H. J. (Theology today, 2012)
The article discusses critically the hermeneutical concept of the document “A Treasure in Earthen Vessels” by the World Council of Churches. I argue for a concept of an ecumenical hermeneutics of diversity instead of the former paradigm of unity and consensual ecumenism. An ecumenical hermeneutics, understood as a hermeneutics of difference and diversity, is not the continuation by other means of consensual ecumenical agreement as we have hitherto known it, but rather a critical corrective to it.